Ethyl pyruvate exerts combined anti-inflammatory and anticoagulant effects on human monocytic cells - van Zoelen, Marieke A. D.; Bakhtiari, Kamran; Dessing, Mark C.; van ’t Veer, Cornelis; Spek, C. Arnold; Tanck, Michael; Meijers, Joost C.; van der Poll, Tom (Thrombosis and Haemostasis, 2006)
Sepsis is characterized by a concurrent activation of inflammation and coagulation. Recently, recombinant human activated protein C was shown to decrease mortality in patients with severe sepsis presumably due to a combined anti-inflammatory and anticoagulant effect.These promising findings led to a search for other products that influence both the inflammatory and the procoagulant response to severe infection. Ethyl pyruvate (EP) was recently identified as an experimental anti-inflammatory agent during endotoxemia and sepsis. The aim of the present study was to investigate whether EP influences coagulation besides its anti-inflammatory effects. For this we investigated the effects of EP on the expression and function of tissue factor (TF), the principal initiator of coagulation activation in sepsis, in human monocytic (THP-1) cell cultures. EP dose-dependently inhibited the production of tumor necrosis factor (TNF)-α, macrophage inflammatory protein (MIP)-1α and MIP-1β by lipopolysaccharide (LPS)-stimulated THP-1 cells at mRNA and protein level, thereby confirming its anti-inflammatory properties in this in-vitro system.In addition, EP dose-dependently attenuated the increases in TF mRNA levels,TF-protein-surface expression and cell-surface-associated TF activity in LPS-stimulated THP-1 cells. These results demonstrate for the first time that EP is a compound with combined anti-inflammatory and anticoagulant effects.
Keywords: Tissue factor; ethyl pyruvate; sepsis; lipopolysaccharide; THP-1 monocytic cells